Thickness effect on the structure, grain size, and local piezoresponse of self-polarized lead lanthanum zirconate titanate thin films - Melo, M. (2017)
Polycrystalline lanthanum lead zirconate titanate (PLZT) thin films were deposited on Pt/TiO2/SiO2/Si substrates to study the effects of the thickness and grain size on their structural and piezoresponse properties at nanoscale. Thinner PLZT films show a slight (100)-orientation tendency that tends to random orientation for the thicker film, while microstrain and crystallite size increases almost linearly with increasing thickness. Piezoresponse force microscopy and autocorrelation function technique were used to demonstrate the existence of local self-polarization effect and to study the thickness dependence of correlation length. The obtained results ruled out the bulk mechanisms and suggest that Schottky barriers near the film-substrate are likely responsible for a build-in electric field in the films. Larger correlation length evidence that this build-in field increases the number of coexisting polarization directions in larger grains leading to an alignment of macrodomains in thinner films. Published by AIP Publishing.